Sistem Pembatasan Pengunjung Perpustakaan pada Masa Pandemi Covid-19 Berbasis Internet of Things - Setya Yuning Tias, Tri; Bintoro, Jusuf; Djatmiko, Wisnu (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2023)
This research aims to develop a library visitor restriction system based on the internet of things. This research uses a research and development method developed by Borg & Gall with 4 stages, namely: analysis stage, design stage, development stage and testing stage. The results of the research on the library visitor restriction system based on the internet of things can be realized by combining sub-systems including ESP32, RFID reader and tag, 16 X 2 LCD, IR (Infrared) sensor module and servo motor. The test results show that the system can work using an RFID reader to verify library membership, the system is also able to detect the presence of visitors by utilizing an infrared sensor with a reading range of up to 12 cm. The servo motor can also be used well for the process of setting the opening and closing of the barrier door.